EKSISTENSI TARI TOPENG MALANGAN DI PADEPOKAN SENI TARI ASMARABANGUN PAKISAJI MALANG 2010 2019 - Mei Puspita Sari (KRONIK : Journal of History Education and Historiography, 2017)
Malangan Mask Dance is a culture that needs to be observed as time goes by, fewer people are willing to preserve this culture, moreover the influx of foreign cultures makes the younger generation increasingly consider Malang mask dance an ancient and outdated culture. Here it is necessary to review further its existence from the Age after the maestro died until his grandson is managing. Malangan mask dance is a culture that deserves to be maintained and maintained its existence as a cultural heritage from the ancestors for us and posterity in the future. This study aims to (1). Knowing the development of the existence of Malangan Mask Dance (2). knowing the preservation of unfortunate mask danceKeywords: Unfortunate Mask Dance, existence, the role of the younger generation